Effective communication in nursing shift handover: scoping review - Pedro Camilo Calado da Silva; Thallyta Juliana Pereira da Silva; Cynthia Roberta Dias Torres Silva; Josicleide Montenegro da Silva Guedes Alcoforado; Ana Carla Silva Alexandre; Guilherme Guarino de Moura Sá; Khelyane Mesquita de Carvalho (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To map available scientific evidence regarding effective communication during the shift handover in nursing. Methods: Scoping review based on the research question "What scientific evidence is available about effective communication in the safe shift handover in nursing?" The selection of studies took place in November 2023, with searches in the MEDLINE, Embase, Web of Science and LILACS databases, Google Scholar screening and manual search in the references of the documents that were part of the sample, with time lapse from 2004, without language restriction. The evaluation was conducted using the data reduction method. Results: The study identified several barriers in communication during the shift handover of the nursing team, including diversification in documentation and lack of privacy. Errors such as omission of information and lack of time were highlighted. Effective strategies involve early preparation, face-to-face communication, an enabling environment, and the inclusion of the patients in the process. Conclusion: The available scientific evidence on effective communication during safe shift handover in nursing was mapped. The study revealed challenges in nursing communication during the shift handover, emphasizing the need for standardization, early preparation and patients' involvement for better continuity in care.